2019
DOI: 10.3389/fnbeh.2019.00161
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Psychosocial Chronic Stress Model in the Pig Using a Multidisciplinary Approach at the Gut-Brain and Behavior Levels

Abstract: Psychological chronic stress is an important risk factor for major depressive disorder, of which consequences have been widely studied in rodent models. This work aimed at describing a pig model of chronic stress based on social isolation, environmental impoverishment and unpredictability. Three groups of animals of both sexes were constituted. Two were exposed to the psychosocial stressors while receiving (SF, n = 12) or not (SC, n = 22) the antidepressant fluoxet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 101 publications
1
27
1
Order By: Relevance
“…We showed here that the two ingredients used modulated differently both these areas via olfaction only. It would be very interesting to assess their effects in a pig model of chronic psychosocial stress and/or anxio‐depressive symptoms for example, as modulations of the aforementioned brain areas were recently described in this model (Menneson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…We showed here that the two ingredients used modulated differently both these areas via olfaction only. It would be very interesting to assess their effects in a pig model of chronic psychosocial stress and/or anxio‐depressive symptoms for example, as modulations of the aforementioned brain areas were recently described in this model (Menneson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Salivary Cort can also detect longer term disruptions, including repeated stressors and social disruption (e.g. Menneson et al., 2019). The response latency (about 5 min) and stressor duration (minutes‐to‐lifetime) measurable by salivary Cort is represented in Figure 1.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…We also showed that high-concentration olfactory stimuli induced a higher brain activity (Table 1; Coquery et al, in press). More interestingly, pigs with a psychosocial stress had lower brain responses in the right hippocampus compared to unstressed control pigs, as well as lower magnetic resonance spectroscopy-estimated neuronal density in the hippocampus, which suggested an impact of the internal state on cognitive and limbic processes at the brain level (Table 1; Menneson et al, 2019).…”
Section: Val-lailletmentioning
confidence: 99%